Essential oil and its nanoemulsions from cymbopogon citratus as effective herbal larvicide against malaria vector, Anopheles stephensi liston. (Funded Work) - MAYAKRISHNAN VIJAY; ARULSAMY JEBANESAN; JAYAPAL SUBRAMANIAM (International Journal of Pharma and Bio Sciences, 2019)
Malaria is a mosquito-transmitted disease, which is one of the most prevalent diseases in the tropical world. It is caused by the malarial parasite, Plasmodium falciparum which is transmitted to humans through the bite of the Anopheles mosquito. Lemon grass oil (Cymbopogon citratus) based nanoemulsion has been developed for large field breeding mosquitoes like An. stephensi. Lemon grass oil nanoemulsion was formulated in different ratios comprising of lemon grass oil, surfactants and water by using ultrasonication. The ratio of lemon grass oil (90%) water (2.5%) and surfactants Tween-20 (2.5%) was found to be stable. The lemon grass oil nanoemulsion was characterized by dynamic light scattering and the PDI (polydispersity index) of the nanoemulsion was found to be 0.02. Lemon grass oil nanoemulsion was screened for its efficacy against An. stephensi. The bioassay showed an LC50 3.30 ppm and LC90 8.70 ppm, respectively after 24 h of exposure. The nanoemulsion was diluted in distilled water at various concentrations. The concentration expressed as Cymbopogon citratus essential oil content on aqueous media. A botanical nanoformulation has been developed which is biodegradable, environment and user friendly approaches for the vector control programme.